(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2022)
The objective of this paper is to analyze the consequences of the economic crisis accentuated by the Covid-19 pandemic in the Brazilian Social Security. Therefore, it will study the relationship between the increase of unemployment and informal work rates, especially the digital labour platforms, and the social protection. Finally, it will present statistics relating to the productivity of INSS during the pandemic.